Association between airborne particles and meteorological parameters in Arak industrial city - Hamed Mir Hosseini (Tehran University of Medical Sciences, 2021)
Introduction: By crossing the borders of cities and countries, air pollution is now a global problem so that it can be claimed that there is no sound and clean air. This study aimed to investigate the effect of meteorological parameters on the concentration of particulate matter (PM2.5 and PM10) in the air of Arak city.